A case with burning mouth syndrome followed by dementia with Lewy bodies: a case report - Watanabe, Motoko; Araki, Wataru; Takao, Chihiro; Maeda, Chizuko; Tominaga, Risa; Kimura, Yasuyuki; Nayanar, Gayatri; Tu, Trang Thi Huyen; Asada, Takashi; Toyofuku, Akira (Frontiers in Psychiatry, 2024)
Burning mouth syndrome (BMS) is characterized by persistent oral burning sensations without corresponding organic findings. Dementia with Lewy bodies (DLB) is a common type of dementia and generally presents visual hallucination and parkinsonism as motor dysfunction besides cognitive decline. In this case report, we present a case in which DLB emerged during the treatment for BMS, with a relatively positive outcome for BMS. A 74-year-old female complained of burning pain in her mouth and a subsequent decrease in food intake. Following a diagnosis of BMS, pharmacotherapy was initiated. BMS was much improved with mirtazapine 15mg and aripiprazole 1.0mg, leading to the restoration of her food intake by day 180. However, BMS flared up again triggered by deteriorating physical condition of herself and that of her husband. With aripiprazole 1.5mg and amitriptyline 25mg, her BMS gradually improved by day 482. However, by day 510, an increase in anxiety was noted, accompanied by the occasionally misidentification of her husband on day 566. Her cognitive impairment and disorientation were also reported by her husband on the day 572, she was then immediately referred to a neurologist specialized dementia and diagnosed with DLB on the day 583. Her treatment was adjusted to include the prescription of rivastigmine which was titrated up to 9.0mg. Considering the potential impact of amitriptyline on cognitive function, it was reduced and switched to mirtazapine; however, her oral sensations slightly got worse. Following the consultation with her neurologist, amitriptyline 10mg was reintroduced and aripiprazole was discontinued on day 755. Remarkably, BMS gradually improved without deteriorating DLB. This case indicated the reaffirmed necessity of careful interviews for changes in daily life not only with the patients but also with their families through the medical assessments. It highlights the vigilance regarding potential cognitive decline underlying or induced as an adverse event especially when treating elderly patients with BMS. While the interaction between BMS and DLB remains unclear, this case underscores the importance of prudent diagnosis and constructing collaboration with specialists in managing BMS with the early phase of DLB.